IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI KEUANGAN NOMOR 199/PMK.010/2019 TENTANG KETENTUAN KEPABEAN, CUKAI, DAN PAJAK ATAS IMPOR BARANG KIRIMAN DI KOTA BATAM - Alvin Asfareza; Febri Yuliani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
In Law Number 44 of 2007 Batam City is designated as a port and free trade area. In this free trade area, some barriers to trade such as tariffs and quotas are abolished. This makes Batam City considered to be able to increase imports in Indonesia and can reduce domestic production. Therefore, the government issued Minister Of Finance Regulation Number 199/Pmk.010/2019 Regarding Provisions On Customs, Excise And Tax On Import Of Parcel. The research objective is to analyze the implementation of PMK No. policy. 199 in Batam City. This study uses qualitative research methods with data collection techniques of observation, interviews, and documentation. This study uses the theoretical basis proposed by Donald Van Meter and Carl Van Horn. The results of this study indicate that The Implementation Policy Of The Minister Of Finance Regulation Number 199/Pmk.010/2019 Regarding Provisions On Customs, Excise And Tax On Import Of Parcels In The City Of Batam has gone quite well, but in its implementation there are still obstacles and rejections from small/medium enterprise and expedition entrepreneurs in Batam City.